Aransemen Lagu Buku Ende No.471 Hupillit Jesus Dongan Ki Pada Permainan Kuartet Saxophone Di GKPI Pagar Beringin Permai - Lisper Sihombing; Robert K.A Simangunsong; Testi Bazarni Zebua (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This thesis discusses the presentation of the arrangement of the song Hupillit Jesus Dongan Ki which is found in ende book number 471 and logu book number 318 by Karl Kuhlo. The author presents this arrangement in the form of a saxophone quartet instrument, namely soprano saxophone, alto saxophone, tenor saxophone and baritone saxophone. This production uses a 4/4 time signature and the basic note F = do with Andante tempo (MM 85). The author worked on this song in the form of a saxophone quartet, while maintaining the original melody of this song which was sung by the soprano saxophone. However, for alto, tenor and baritone saxophone, each melody is the result of developing ideas from the main melody. The development of the form of melody, rhythm, tempo, harmony, dynamics, in this arrangement aims to deepen the message and meaning of the song. According to the title of the research, the researcher used a qualitative descriptive research method, namely by describing the arrangement of the song Hupillit Jesus Dongan Ki by Karl Kuhlo on a saxophone quartet playing at GKPI Pagar Beringin Permai, which was carried out in August - September 2023. By conducting observations and interviews, looking for literature and several sources related to arranging and saxophone, and arranging in writing. The result of this research is a new presentation concept for the song Hupillit Jesus Dongan Ki in the form of a saxophone quartet instrument. The different sound characteristics of each saxophone instrument make the harmony of the song even more beautiful. Improvised forms of alto, tenor and baritone saxophone melodies can fill in any gaps in the main melody, thereby enriching the harmony of the song Hupillit Jesus Dongan Ki..